Conditions for one-valued solvability of nonlinear stationary heat-conduction problems - Zhernovoi, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish conditions for existence and uniqueness of nonnegative solutions of nonlinear stationary heat-conduction problems, the Dirichlet, problem and the Neumann one, with regard for the dependence of the heat-conduction coefficient and inner heat sources on temperature.